Odpowiedź :
Odpowiedź:
w(x) = -3x⁴ + 5x³ + x² - 8
u(x) = x⁵ - 5x³ + 4x + 8
a) w(x) + u(x)
-3x⁴ + 5x³ + x² - 8 + x⁵ - 5x³ + 4x + 8 = x⁵ -3x⁴ + x² + 4x
b) w(x) - u(x)
-3x⁴ + 5x³ + x² - 8 - (x⁵ - 5x³ + 4x + 8) = - 3x⁴ + 5x³ + x² - 8 - x⁵ + 5x³ - 4x - 8 = = - x⁵ - 3x⁴ + 10x³ + x² - 4x - 16
c) w(x) - 2u(x)
-3x⁴ + 5x³ + x² - 8 - 2 (x⁵ - 5x³ + 4x + 8) =
= - 3x⁴ + 5x³ + x² - 8 - 2x⁵ + 5x³ - 8x - 8 = - 2x⁵ - 3x⁴ + 10x³ + x² - 8x - 16
d) 3u(x) - w(x)
3 (x⁵ - 5x³ + 4x + 8) - (-3x⁴ + 5x³ + x² - 8) =
= 3x⁵ - 15x³ + 12x + 24 + 3x⁴ - 5x³ - x² + 8 = 3x⁵ + 3x⁴ - 20x³ - x² + 12x + 32